2005
DOI: 10.1159/000086149
|View full text |Cite
|
Sign up to set email alerts
|

Effect of an Oat Bran-Rich Supplement on the Metabolic Profile of Overweight Premenopausal Women

Abstract: Background/Aims: A healthy diet is a key factor in the prevention of cardiovascular disease, the leading cause of death for women in industrialized countries. In this regard, soluble fibers may have beneficial effects on the plasma lipoprotein/lipid profile. The objective of the present study was to investigate the plasma lipoprotein/lipid response to dietary fibers in overweight premenopausal women within a randomized controlled trial. Methods: Following a 2-week run-in phase, 34 premenopausal women (age: 22–… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
21
0
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(22 citation statements)
references
References 57 publications
0
21
0
1
Order By: Relevance
“…However, some authors (e.g. Brown et al 1999;Keogh et al 2003;Robitaille et al 2005) reported no significant changes in the cholesterol levels after the fibre diet. β-glucans show also positive cardio- (Keogh et al 2003;Stephens 2005) and subsequently glycaemic reactions (Cavallero et al 2002;Tappy 2006;Alminger & Eklund-Jonsson 2008;Nazare et al 2009) beneficial for the overweight humans and patients with type 2 diabetes ).…”
Section: Physiological Effects Of Cereal β-Glucansmentioning
confidence: 99%
“…However, some authors (e.g. Brown et al 1999;Keogh et al 2003;Robitaille et al 2005) reported no significant changes in the cholesterol levels after the fibre diet. β-glucans show also positive cardio- (Keogh et al 2003;Stephens 2005) and subsequently glycaemic reactions (Cavallero et al 2002;Tappy 2006;Alminger & Eklund-Jonsson 2008;Nazare et al 2009) beneficial for the overweight humans and patients with type 2 diabetes ).…”
Section: Physiological Effects Of Cereal β-Glucansmentioning
confidence: 99%
“…The subjects received 2 oat branenriched muffins (14 g each) daily for a month. The supplementation improved plasma HDL cholesterol levels, mean being 11.2% (Robitaille, Fontaine-Bisson, Couture, Tchernof, & Vohl, 2005). The effects of oat bran on plasma cholesterol, markers of inflammation, eNOS expression and development of atherosclerosis were examined in mice model.…”
Section: Oat (Avena Sativa)mentioning
confidence: 99%
“…Fifteen randomised controlled trials in 17 publications were identified that presented evidence on oat bran/oatmeal, barley fibre or β-glucan supplements in relation to energy intake (Whyte et al, 1992;Abrahamsson et al, 1994;Johnston, 1998;Reynolds et al, 2000;Davy et al, 2002a;Davy et al, 2002b;Kerckhoffs et al, 2003;He et al, 2004;Robitaille et al, 2005;Chen et al, 2006;Keenan et al, 2007;Theuwissen & Mensink, 2007;Maki et al, 2007a;Maki et al, 2007b;Smith et al, 2008;Sundberg, 2008;Kohl et al, 2009), twelve of which were included in a meta-analysis (Whyte et al, 1992;Abrahamsson et al, 1994;Reynolds et al, 2000;Davy et al, 2002a;Kerckhoffs et al, 2003;Robitaille et al, 2005;Chen et al, 2006;Theuwissen & Mensink, 2007;Maki et al, 2007a;Maki et al, 2007b;Smith et al, 2008;Sundberg, 2008). Two trials reported energy intake data in two publications (Davy et al, 2002a;Davy et al, 2002b) and (He et al, 2004;Chen et al, 2006).…”
Section: Energy Intakementioning
confidence: 99%